Rescue therapy for hypercapnia due to high PEEP mechanical ventilation in patients with ARDS and renal failure. Issue 6 (13th December 2018) - Grant, April A.; Hart, Valerie J.; Lineen, Edward B.; Forsberg, Brian C.; Klima, Alan; Mirsaeidi, Mehdi; Schulman, Ivonne H.; Badiye, Amit; Vianna, Rodrigo M.; Patel, Amit; Loebe, Matthias; Ghodsizad, Ali
Abstract: Extracorporeal removal of carbon dioxide in patients experiencing severe hypercapnia due to lung protective mechanical ventilation was first described over four decades ago. There have been many devices developed and described in the interim, many of which require additional training, resources, and staff. This manuscript describes a readily available and relatively simple adjunct that can provide partial lung support in patients with acute respiratory distress syndrome complicated by severe hypercapnia and acute kidney injury requiring dialysis.